Differential Analysis of O-(2- hydroxypropyl) cellulose by Using Two-Dimensional 1H-NMR Spectroscopy - Naotaka Sakamoto; Edmont Stoyanov (Archive of Biomedical Science and Engineering - Peertechz Publications, 2020)
Two-dimensional 1H-NMR is used to determine the intra-molecular interactions of O-(2-hydroxypropyl) cellulose (HPC) in aqueous (D2O), DMF and DMSO solutions. Four grades HPC with different molecular weights are analyzed by using NOESY (Nuclear Overhauser Effect Spectroscopy) for proton-proton cross-interactions. A strong dependence of the polymer chain structure on the HPC Molecular Weight (MW) is overserved. The lower MW HPCs exist in solutions as a more linear chain showing less proton-proton interactions whereas the higher MW HPCs are more twisted and bended and form a tangled molecule mess with very intensive interactions between the -CH3, -CH2- and -C-H protons. From all the grades, the ultra-low molecular weight HPC-UL (MW 20,000) revealed the weakest proton-proton cross-relaxations and exists in solutions probably only as an almost linear chain polymer.